Non-medical costs of colonoscopy - Petryszyn, Paweł W.; Kempiński, Radosław; Michałowicz, Jerzy; Poniewierka, Elżbieta (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Colorectal cancer is one of the most common malignancies in Europe and North America. Colonoscopy done every 10 years beginning at age 50 is the preferred method of screening. In Poland and some other countries examinations are offered to subjects free of charge. However, as well as direct medical costs there are direct non-medical costs, which include the cost of transportation and costs related to caregivers’ time, and indirect costs, which are costs related to patients’ time. These costs essentially augment the total societal costs of colonoscopy.